A ruling Zakat ornaments (Journal of the College of Education for Women, 2019)
The research topics important topic of jurisprudence worship, a ruling Zakat ornamentsprepared for use, and touched the odds scholars in it. Stroll scholars say that there is no Zakaton ornaments prepared for use have reported their evidence they and the owners say the otherof those who say should be directed to pay zakaat, and discuss those views and statementDafeeha of Sahihaa, and came up with a summary then, showed where the prevailing viewthat I see in agreement of the transferee and reasonable. Ask Him to show us the right, andthank God.